Immunohistochemical Demonstration of COX2 in Various Lesions of Oral Cavity: Immunohistochemical Expression of COX-2 in Oral Lesions - Zafar, Salman; Qamar, Nazia; Khan, Hurtamina; Shahid, Madeeha; Sundus, Sadia; Malik, Farah (Pakistan Journal of Health Sciences, 2025)
Cyclooxygenase enzyme facilitates the conversion of arachidonic acid into pro-inflammatory compounds, resulting in formation of prostaglandins, which contributes substantially to the carcinogenic process. Objective: To analyze the immunohistochemical COX2 enzyme expression in various lesion of oral cavity. Methods: A total of 60 formalin fixed, paraffinized blocks (including 10 healthy oral mucosa cases, 10 cases of leukoplakia. 10 cases of oral sub mucosal fibrosis, 10 cases of dysplasia, 10 cases of well differentiated carcinoma, 10 cases of highly aggressive invasive squamous carcinoma) were randomly selected during the period of Jan, 2022 till Dec, 2023. Immunohistochemistry was done on each case for analyzing COX2 expression. Data was statistically analyzed by using chi square test. P value < 0.05 was taken as substantial. Result: It was found that the expression level was high in invasive carcinoma as compared with other oral lesion. Conclusion: Present study strongly supported the involvement of COX2 in the advancement of precancerous lesions of oral cavity to malignant one.